the simplified form of
![( \sqrt{7 + 4 \sqrt{3} } - \sqrt{3} ( \sqrt{7 + 4 \sqrt{3} } - \sqrt{3}](https://tex.z-dn.net/?f=%28+%5Csqrt%7B7+%2B+4+%5Csqrt%7B3%7D+%7D+-++%5Csqrt%7B3%7D+)
Answers
Answered by
2
Heya!!✋
Here is your answer.
-------------------------------------------
Given that,
√(7+4√3) - √3
=> √ (2²+2×2×√3+√3²)-√3
=> √ (2+√3)² - √3
=> 2+√3-√3
=> 2 [Answer]
Hope it will help you, friend :)
Here is your answer.
-------------------------------------------
Given that,
√(7+4√3) - √3
=> √ (2²+2×2×√3+√3²)-√3
=> √ (2+√3)² - √3
=> 2+√3-√3
=> 2 [Answer]
Hope it will help you, friend :)
Similar questions